THE ROLE OF SMALL INNOVATIVE ENTERPRISES IN THE DEVELOPMENT AND MARKET LAUNCH OF INNOVATIVE DRUGS - A. A. Semin (Разработка и регистрация лекарственных средств, 2019)
The features of new products market launch by small innovative enterprises are the theme for careful study. The reason is the problems that Russia has nowadays - the need for reindustrialization, the economic diversification and the import substitution for improving the competitiveness of domestic producers, the necessity for increase of real employment, the reduction of qualified personnel’s leak. It acquires special relevance in the pharmaceutical industry as it is one of the most high-technology industries. The innovative small and medium-sized enterprises (SME) could play a big role in solving these problems, as they could initiate innovations, lead (alone or in a partnership with larger companies) high-technology research and development, promote the commercialization of innovations.